63‐2: A Novel Touch‐control Method with Partial Scanning for LC, OLED, and Hybrid Displays using an Oxide Semiconductor. Issue 1 (2nd June 2017) - Takahashi, Kei; Kusunoki, Koji; Watanabe, Kazunori; Okano, Tatsuya; Suematsu, Yui; Ikezoe, Satoshi; Hatsumi, Ryo; Misawa, Chieko; Dobashi, Masayoshi; Nakada, Masataka; Katayama, Masahiro; Yamazaki, Shunpei
Abstract : A touch‐control method using partial scanning is devised for various displays using an oxide semiconductor in their backplanes. This method enables sensing results by long‐term consecutive touches to be displayed in real time, offering features of idling stop driving with low power consumption and high sensing accuracy.